Scenario-guided policy planning in Uganda - Rutting, Lucas; Tumuhereze, Martin; Ampaire, Edidah L.; Muchunguzi, Perez; Acosta, Mariola; Okiror, John Francis; Asten, Piet J.A. van (2016)
Using socio-economic scenarios in policy formulation allows for an anticipatory approach to governance processes and the formulation of policies/plans that take into account future uncertainty To fully benefit from the dividends of scenario planning in the Ugandan context, there is need to build the scenario-guided planning capacity of both public and private sectors. There is need for follow up and continuous engagement with government officials responsible after the review process to enable inclusion of recommendations generated into the final policy documents. In some cases, the abstract nature of national policy statements limits the level of detail, hence detailed scenario guided recommendations and information may not easily fit in the existing policy formats. The approach is new and requires extra awareness creation not only for the government officers who draft policies but also for other major policy actors such as the political leadership who approve the policies.